Comparing Vertical Distributions of Chl-a Fluorescence, Marine Snow, and Taxon-Specific Zooplankton in Relation to Density Using High-Resolution Optical Measurements - Briseño-Avena, Christian; Prairie, Jennifer C.; Franks, Peter J. S.; Jaffe, Jules S. (Frontiers in Marine Science, 2020)
Interactions between predators and their prey are important in shaping planktonic ecosystems. However, these interactions are difficult to assess in situ at the spatial scales relevant to the organisms. This work presents high spatial resolution observations of the nighttime vertical distributions of individual zooplankton, chlorophyll-a fluorescence, and marine snow aggregates in stratified coastal waters of the Southern California Bight. Data were obtained using a planar laser imaging fluorometer (PLIF) augmented with a shadowgraph zooplankton imaging system (O-Cam) mounted along with ancillary sensors on a free-falling platform. Fluorometer and PLIF sensors detected two well-defined and distinct peaks: the subsurface chlorophyll maximum (SCM) and a fluorescent particle maximum (FPM) dominated by large aggregates. The O-Cam imaging system allows reliable estimates of concentrations of crustacean and gelatinous zooplankton group; we found that grazers and their predators had well-structured nighttime distributions in and around the SCM and FPM in ways that suggested predator avoidance at the peak of the SCM and immediately above the FPM (where predatory hydromedusae, and to some degree euphausiids, were primarily located). Calanoid copepods were found above the SCM while cyclopoids were associated with the FPM. The locations of predator and grazer concentration peaks suggest that their dynamics may control the vertical gradients defining the SCM and FPM.